High Current Anxiety Symptoms, But Not a Past Anxiety Disorder Diagnosis, are Associated with Impaired Fear Extinction - Duits, Puck; Cath, Danielle C.; Heitland, Ivo; Baas, Johanna M. P. (Frontiers in Psychology, 2016)
Although impaired fear extinction has repeatedly been demonstrated in patients with anxiety disorders, little is known about whether these impairments persist after treatment. The current comparative exploratory study investigated fear extinction in 26 patients treated for their anxiety disorder in the years preceding the study as compared to 17 healthy control subjects. Fear-potentiated startle and subjective fear were measured in a cue and context fear conditioning paradigm within a virtual reality environment. Results indicated no differences in fear extinction between treated anxiety patients and control subjects. However, scores on the Beck Anxiety Inventory across all participants revealed impaired extinction of fear potentiated startle in subjects with high compared to low anxiety symptoms over the past week. Taken together, this exploratory study found no support for impaired fear extinction in treated anxiety patients, and implies that current anxiety symptoms rather than previous patient status determine the success of extinction.